PEMBUATAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF DENGAN MENGGUNAKAN MACROMEDIA FLASH - Ida M. Hutabarat; Irfan Wahyudi; Mingsep R. Sampebua (JURNAL PENGABDIAN PAPUA, 2022)
The use of learning media can improve the effectiveness and efficiency of the learning process. The solutions offered to partners are; help partners illustrate something abstract in mathematics that requires visualization or animation in writing, especially in the form of images. The methods used for solutions to problems faced by partners and to support the success of the program are in the form of lectures, questions and answers, demonstrations and exercises/practices. Participants who have attended the training will put into practice directly the results of the training they received and create learning media with the guidance of the trainer so that participants can create interactive mathematics learning media using Macromedia Flash, and can develop their work according to their imagination. The results of the implementation of PKM activities were felt by the service team and the training participants were very satisfying. With an indicator of the arrival of participants in each meeting and the enthusiasm of the participants. The results of the practice carried out were successful or maximal.Keywords:  training; Practicum methods; Chemistry learning; SMA PGRI Jayapura